Limitation of Liability of the Rail Carrier Operator Based on CIM Rules (Global Journal of Human-Social Science, 2012)
Generally accepted rule of CIM like other conventions about carrier operator is that in case of any damage related to contract of carriage the liability of carrier such as railway or rail transportation institutes will not exceed a certain ceiling except those cases predicted in regulations The ceiling of carrier liability is payment of seventeen units of account at most for each kilogram of non-net weight of goods
Keywords: Limitation of Liability; Compensation; Units of Account; COTIF Convention; International Monetary Fund (IMF)